Pelatihan dan Pendampingan Pembuatan Video Potensi Eko-Agrowisata Sebagai Media Virtual Tour : Desa Wisata Cisaat, Kabupaten Subang, Jawa Barat - Revi Agustin Aisyianita; Rahmat Darmawan; Jenal Abidin; Lala Siti Sahara; Rezka Fedrina (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Training and Assistance in Making Videos of the Potential of Eco-Agrotourism as a Virtual Tour Media The Community Service Integrated Real Work Lecture (PKM – KKN) activity held in Cisaat Village, Subang, aims to (1) provide an understanding of the concept of virtual tourism as an alternative new tourism product; (2) conducting training and assistance in making videos and simple editing techniques: (3) conducting training and mentoring on the use of Zoom as a virtual tourism support tool. The results of this mentoring activity include: (1) increasing public understanding of virtual tourism; (2) the implementation of training activities for making and editing simple videos (3) the implementation of training activities on the use of Zoom as a virtual tour support tool. At the end of the program, the evaluation results showed a positive response from all participants.